PENGARUH CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO SERTA NON PERFORMING LOAN TERHADAP RETURN ONASSET PADA LEMBAGA PERKREDITAN DESA SE-KECAMATAN NEGARA - ., I Gede Javawan; ., Gede Putu Agus Jana Susila, S.E., MBA.; ., Ni Luh Wayan Sayang Telagawathi, S.E., M (Jurnal Manajemen Indonesia, 2019)
Penelitian ini bertujuan untuk menguji pengaruh (1) capital adequacy ratio dan long to deposit ratio serta non performing loan secara simultan terhadap return on assets, (2) capital adequacy ratio terhadap return on assets, (3) long to deposit ratio terhadap return on assets, (4) non performing loan terhadap return on assets. Desain penelitian yang digunakan adalah kuantitatif kausal. Subjek penelitian ini adalah LPD di Kecamatan Negara dan objek penelitianya adalah capital adequacy ratio, long to deposit ratio, non performing loan dan return on assets. Data dikumpulkan dengan pencatatan dokumen dan analisis dengan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa (1) ada pengaruh secara simultan capital adequacy ratio dan long to deposit ratio serta non performing loan terhadap return on assets sebesar 59,8%, (2) ada pengaruh negatif dan tidak signifikan capital adequacy ratio terhadap return on assets sebesar 6,6%, (3) ada pengaruh positif dan signifikan long to deposit ratio terhadap return on assets sebesar 18,5%, (4) ada pengaruh negatif dan signifikan non performing loan terhadap return on assets sebesar 53,4%. Kata Kunci : capital adequacy ratio, loan to deposit ratio, non performing loan dan return on assets The research has a purpose to examine the effect of, (1) capital adequacy ratio, long to deposit ratio and non performing loan simultaneously on the return on assets, (2) capital adequacy ratio on the return on assets, (3) long to deposit ratio on the return on assets, (4) non performing loan on the return on assets. The research design used was quantitative causal. The subject of research were LPD in Negara Districts, and the object of this research were capital adequacy ratio, long to deposit ratio, non performing loan and return on assets. The data was obtained by documentation technique, and analyzed using multiple linear regression. The result of this research shows that (1) there was a effect simultaneously from their capital adequacy ratio, long to deposit ratio, and non performing loan on the return on assets about 59,8%, (2) there was a negative effect and no significant capital adequacy ratio on the return on assets about 6,6%, (3) there was a positive effect and significant long to deposit ratio on the return on assets about 18,5%, (4) there was a negative effect and significant non performing loan on the return on assets about 53,4% keyword : capital adequacy ratio, long to deposit ratio, non performing loan and return on assets